2022
DOI: 10.1001/jamaoto.2021.3672
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for Patients With Unilateral Sudden Hearing Loss in the COVID-19 Era

Abstract: IMPORTANCE Developing a telemedicine tool to discriminate between patients who need urgent treatment for sudden sensorineural hearing loss (SSNHL) from those who do not takes on special importance during the COVID-19 pandemic.OBJECTIVE To explore the feasibility of a telemedicine model to assist in the evaluation of new-onset unilateral sudden hearing loss (SHL) among patients who do not have access to medical resources, especially during the COVID-19 pandemic.DESIGN, SETTING, AND PARTICIPANTS This prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In this context, tele-audiometry has become a workable option for audiometric examination, with a high level of accuracy that is not significantly different from traditional audiometric testing ( 41 ). A study by Shilo et al based on smartphone vibration and uHear App hearing tests also confirmed that the telemedicine model for diagnosing SSNHL is valid and reliable ( 42 ). In addition, some improvements can be made to the hearing test technologies to minimize contact with the patient.…”
Section: Discussionmentioning
confidence: 78%
“…In this context, tele-audiometry has become a workable option for audiometric examination, with a high level of accuracy that is not significantly different from traditional audiometric testing ( 41 ). A study by Shilo et al based on smartphone vibration and uHear App hearing tests also confirmed that the telemedicine model for diagnosing SSNHL is valid and reliable ( 42 ). In addition, some improvements can be made to the hearing test technologies to minimize contact with the patient.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, large populations in the low economic countries may not have accessibility to hearing care services due to the nancial inability of their health sectors to establish audiology clinics, which require medical devices, furniture, construction, and other overhead costs [4][5][6][7]. An a ordable and accessible alternative to tackle these concerns is using the available technology in smartphones and low-cost sensors [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Hearing tests were not routinely conducted, and confirmed COVID-19 patients were even less likely to be sent to undergo audiometric studies. At-home and mobile SSNHL tests have been developed and seem to be reliable but could not eventually replace an objective audiometry ( 18 ).…”
Section: Discussionmentioning
confidence: 99%